If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(5x + 1) = 5x + -6x Reorder the terms: 8(1 + 5x) = 5x + -6x (1 * 8 + 5x * 8) = 5x + -6x (8 + 40x) = 5x + -6x Combine like terms: 5x + -6x = -1x 8 + 40x = -1x Solving 8 + 40x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 8 + 40x + x = -1x + x Combine like terms: 40x + x = 41x 8 + 41x = -1x + x Combine like terms: -1x + x = 0 8 + 41x = 0 Add '-8' to each side of the equation. 8 + -8 + 41x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 41x = 0 + -8 41x = 0 + -8 Combine like terms: 0 + -8 = -8 41x = -8 Divide each side by '41'. x = -0.1951219512 Simplifying x = -0.1951219512
| c/2+1=9/2 | | -6x=-3x+12 | | 6x^2-17x=17 | | 17+(828-305-4021y)=3-40 | | (1/7)(x+21)=-6 | | f(x)=-4x^2+9x+7 | | 5x-3=7x-25 | | -0.7x+9.89=-0.9x+4.69 | | 4x-13=-6x | | 50-7x=-34 | | (3/4)x-22=9 | | -0.5x+6.47=-0.7x+2.47 | | 5/6x=2-11/12x | | 11(4X-4)+7=8X-9 | | 8x+2.3=6x+2.3 | | 13-1x= | | 6x1x2/3x7 | | 6-2x=5x-9+9 | | -11-7x=-60 | | 5x-7x-13=-2x+6-13 | | 29=-16+9x | | 7x2/3-1x6 | | 6x+4(1x-3)=48 | | 4-3(x+3)=11-7(5-2x) | | 32x^2+28xy-15y^2=0 | | 11X/5(4-7)=6X+8 | | 15+3x=x-3 | | 0.5x+6.47=-0.7x+2.47 | | -5w=2w-21 | | 8x-12-2x+6=42 | | 6(3x+9)=18x+54 | | 306/t-22=13 |